Fuel An Ecocritical History - Scott, Heidi C. M. (Environmental Cultures, 2018)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Fuel: An Ecocritical History is the first book to chart our changing attitudes to fuel and energy through the literature and culture of the modern era, focusing on the 18th-century to the present. Reading a wide range of writers from Blake, Austen and Dickens to Upton Sinclair and Edward Abbey, Heidi Scott explores how our move from a pre-industrial reliance on biomass and elemental energy sources to our current dependence on the fossil fuels of coal, oil and natural gas have fundamentally shaped human identity and culture. The book's Anthropocene perspective reshapes our view of energy history and climate change, and Fuel looks forward to ways in which we can reimagine our culture away from the fossil fuel paradigm towards a more sustainable energy future driven by renewable, elemental energy.